Reconstruction of the Practice of Siyasa Syar'iyyah During the Islamic Empire's Relevance to the Practice of Sharia Financing CWLS Retail in Indonesia - Putra, Haris Maiza; Ahyani, Hisam; Naisabur, Nanang; Muharir, Muharir; Naisabur, Chikal Anugrah Putra (Institut Agama Islam Negeri Curup, 2023)
The purpose of this study is to analyze the reconstruction of Islamic sharia implementation policies during the Islamic Empire in Indonesia from the perspective of siyasah syar'iyyah and their relevance to Indonesian government policies in regulating Islamic financing instruments in Cash Waqf Linked Retail Sukuk (CWLS Retail). The statutory approach and descriptive analysis are used in this research. Sources of data were obtained from various literary materials both from books, journals and the internet, as well as other relevant sources regarding the politics of Islamic law (siyasah syar'iyyah) during the Islamic period and its relevance to the regulation of Islamic financing instruments in Indonesia, especially with regard to the application of retail sukuk cash waqf (CWLS Retail). The results of the study show that first, the political application of Islamic law during the Islamic empire in Indonesia was carried out through the politics of the king's power (ruler). Second, the application of political Islamic law has relevance to current Indonesian government policies, namely in regulating Islamic financing instruments for Cash Linked Retail Sukuk (CWLS Retail), where the Government through various Islamic policies is embodied through laws, government regulations, MUI Fatwa, and other regulations. However, implementing this policy requires 6 variables of Islamic politics (siyasah syar'iyyah) in the opinion of Ibn Khaldun, namely mutual synergy between law, government, society, economy, development and justice.